Pengaruh Kualitas Produk, Harga, dan Promosi terhadap Keputusan Pembelian pada Aplikasi Tiktok Shop - Devi Nurchasanah; Ambar Lukitaningsih; Putri Dwi Cahyani; Ida Bagus Nyoman Udayana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The research entitled The Effect of Product Quality, Price, and Promotion on Purchase Decisions in the Tiktok Shop Application is the result of a quantitative study that aims to answer questions about the effect of product quality, price, and promotion on purchasing decisions in the Tiktok Shop application. The research methodology used is quantitative research using survey methods. sampling technique using google form with 75 respondents. Data collection techniques used questionnaires which were processed using SPSS version 20. Data analysis used multiple linear regression. The results of the study show that product quality has a partial effect on purchasing decisions in the TikTik Shop application. Research shows that customer expectations on the TikTok Shop application are valid and significant for purchase decisions and customer satisfaction. Keywords: product quality, price, purchase decision